Fundef (1996-2006): a remuneração dos professores do ensino fundamental da rede pública municipal de Natal/RN - Araújo, Fádyla Késsia Rocha de (2012)
This work discusses about the teacher salary in the primary school after the creation of the Fundo de Manutenção e Desenvolvimento do Ensino Fundamental e Valorização do Magistério (Fundef), in the public schools in Natal/RN, from 1996 to 2006. The salary is considered one of the politic dimensions of the valorization of teaching. We aim to analyze the implication of this fund to the teacher remuneration, with different levels of training, in the early career, comparing it to the annual minimum salary, during the same period. This study has a historic-critic approach, establishing the relationship between the elements into a particular context (valorization of teaching/ teacher salary) and the elements from general contexts (financing/ Fundef). Analyzing data of the teacher remuneration from municipal payroll and comparing them to the annual national minimum salary gave us the result that the teachers, in their early career, do not have remuneration with a satisfactory evolution. Teachers that finished high school received until three minimum salaries before the creation of Fundef (1996-1997), after that (in 1998) they received under two minimum salary. In addition to this, independently of the level of the teacher training, their remuneration is under three minimum salaries. Hence, we can infer that the politic of funds is distant from the ideal to valorize the professional of the municipal teaching